Capacidad adaptativa al cambio climático de los hogares rurales del cantón Zamora, provincia de Zamora Chinchipe, Ecuador - Fajardo Aguirre, Cecilia Marisol (2024)
Climate change is a global phenomenon that affects every part in the world, but its impact affects disproportionally the poorest and most disadvantaged people on the planet. Rural communities are especially vulnerable to climate change due to their dependence on natural resources, lack of information and resources to face these challenges. Nonetheless, the adaptive capacity of these households regarding climate change is still unknown, which makes it difficult to make appropriate decisions to mitigate impact. The main question that guides this research is: What is the adaptive capacity of rural households in the Zamora canton? With the purpose of addressing this knowledge deficit, a research was carried out in the parishes of Timbara and Guadalupe in the Zamora Chinchipe canton to evaluate the adaptive capacity, building an index that considers three socio-economic, institutional and socio-ecological dimensions, adapting prior methodologies. As a result of this research, households in the rural communities of Timbara and Guadalupe show a medium and low level of adaptive capacity; those that obtained the highest score in the adaptive capacity index are characterized by having a higher level of education, access to credit, greater diversification of economic income, higher income and a lower proportion of people under 15 and over 65 years of age. Therefore, lack of education, elderly age and limited economic diversification increase the vulnerability of households to climate change; thus, it is crucial to implement education programs and inclusive policies to strengthen adaptive capacity in rural communities.